Chlorpromazine And Graft Survival An Experimental Study - Dr. N.K. Keswani; Dr. Tatsat Misra; Dr. D.C. Srivastava; Dr. Ajai Bansal (Indian Journal of Plastic Surgery)
Large number of drugs have been used to make the longer length of the flap to survive in experimental animals. In present study, chlorpromazine has been used in experimental rats. In all, thirty albino rats were experimented. Longer length treated flap survival rate was observed in chlorpromazine group.